STRATEGI OPTIMALISASI CAPAIAN IKU 5 UNIVERSITAS JAMBI: Strategy for Optimizing the Achievements of IKU 5 Universitas Jambi - Romi Kurniadi; Aspita Dyah Fajarsari; Destri Yaldi; Arpizal Arpizal; Mayasari Mayasari (Anterior Jurnal, 2023)
The purpose of this study is to build a strategy model for optimizing the achievement of IKU 5 at Jambi University. The Main Performance Index (KPI) is a benchmark of achievement made by universities in Indonesia. As a highlight, Jambi University's KPI 5 became one of the indicators whose achievement exceeded the target of 142.05%, compared to other KPI achievements. However, this achievement was not accompanied by an increase in achievement growth compared to the previous year. The decline in growth from the previous year was -51.12%. This study uses action research methods. The deepening of the problem is carried out by direct observation and document review. The available information is used as the basis for formulating a strategy model for achieving KPI 5 at Jambi University. The results of the study indicate that the main problems that need to be resolved are related to (a) management of recognition of Lecturer Performance Burden (BKD), (b) internationally recognized research ideas and results, and (c) lecturer participation in conducting research and community service. The strategies developed include (a) planning research outcomes that meet the KPI 5 indicators, (b) improving BKD management, (c) providing incentives, and (d) participation of international academic associations.